2020
DOI: 10.3389/fcell.2020.573987
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Triggered by Fructose Diet Impairs Neuronal Function and Vascular Integrity in ApoE-KO Mouse Retinas: Implications of Autophagy Deficient Activation

Abstract: Metabolic syndrome is a disorder characterized by a constellation of clinical findings such as elevated blood glucose, hyperinsulinemia, dyslipidemia, hypertension, and obesity. A positive correlation has been found between metabolic syndrome or its components and retinopathy, mainly at microvascular level, in patients without a history of diabetes. Here, we extend the investigations beyond the vascular component analyzing functional changes as well as neuronal and glial response in retinas of Apolipoprotein E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(77 reference statements)
2
4
0
Order By: Relevance
“…Finally, in previous studies we found that ApoE-KO mice had higher levels of circulating cholesterol, triglycerides, LDL-cholesterol, and HDL-cholesterol, and increased fasting plasma insulin levels 28 . The increase in fasting insulin was detected at 6 months of age, while the alteration in the lipid profile (high levels of total cholesterol, HDL and LDL cholesterol) was found at 4 months of age and lasted until 6 months of age 28 , 43 , these remaining lipoproteins can undergo lipolysis, generating small-dense LDL, which in turn promotes the formation of aggregated LDL 44 . In the present study, we found that ApoE-KO mice (6 months of age) had increased lipid accumulation in the myocardium detected by BODIPY-stained lipid droplet (Supplementary Fig.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Finally, in previous studies we found that ApoE-KO mice had higher levels of circulating cholesterol, triglycerides, LDL-cholesterol, and HDL-cholesterol, and increased fasting plasma insulin levels 28 . The increase in fasting insulin was detected at 6 months of age, while the alteration in the lipid profile (high levels of total cholesterol, HDL and LDL cholesterol) was found at 4 months of age and lasted until 6 months of age 28 , 43 , these remaining lipoproteins can undergo lipolysis, generating small-dense LDL, which in turn promotes the formation of aggregated LDL 44 . In the present study, we found that ApoE-KO mice (6 months of age) had increased lipid accumulation in the myocardium detected by BODIPY-stained lipid droplet (Supplementary Fig.…”
Section: Resultssupporting
confidence: 50%
“…As animal model, we used male C57BL/6J wild-type mice (Wt) and male Apolipoprotein E-deficient (ApoE-KO) mice on the same background (The Jackson Laboratories, Bar Harbor, ME, United States) 28 . We chose to use male mice to avoid fluctuations in the lipid profiles caused by hormonal cycling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruch membrane and basal membrane of retinal vessels were found thickened leading to an ischemic state which plays a role in cell damage. In contrast, Paz et al [22] showed changes in astrocyte integrity without any Müller cell reactivation via in vivo animal model of MetS. They also demonstrated an increased rate of apoptosis in the GCL and inner nuclear layer.…”
Section: Resultsmentioning
confidence: 88%
“…The obtained cryosections were stored at −20 • C under dry conditions. Immunostaining was performed as described previously [34]. Briefly, cryosections were washed with PBS, blocked with 2% of BSA in PBS containing 0.1% Tween-20 for 1 h, and then incubated ON at 4 • C with the following primary antibodies, respectively: rabbit polyclonal anti-GFAP (1/1000; Dako, Carpinteria, CA, USA), mouse β3 tubulin (1/500; ab78078, Abcam), and goat anti-p75 NTR (1/500; R&D system).…”
Section: Immunofluorescent Detections In Retinal Cryosectionsmentioning
confidence: 99%